posted by kristie .
how would you solve for y in this problem:
would it equal: y= x^3/y - 3 ?
and what about this problem:
would it equal: y = y/x + 5/y - 3?
I would appreciate your help very much!
<<how would you solve for y in this problem:
would it equal: y= x^3/y - 3 ? >>
Your equation is correct but it does not allow you to solve explicitly for y. What you have to do is treat the "x-containing" term as if it were a constant in the quadratic equation:
y^2 + 3y -x^3 = 0
Then use the equation for the root of quadratic equations:
y = [-6 +/- sqrt (9 + 4x^3)]/2
The second question can be handled similarly.